Simplify 3 – b(7b + 2) + 3b – (11 – b).
2 answers:
Answer: -7b2+2b-8
Step-by-step explanation:
I just did the assignment
<span>Simplifying
7b + -4 + 3b + 11 + -1b = 0
Reorder the terms:
-4 + 11 + 7b + 3b + -1b = 0
Combine like terms: -4 + 11 = 7
7 + 7b + 3b + -1b = 0
Combine like terms: 7b + 3b = 10b
7 + 10b + -1b = 0
Combine like terms: 10b + -1b = 9b
7 + 9b = 0
Solving
7 + 9b = 0
Solving for variable 'b'.
Move all terms containing b to the left, all other terms to the right.
Add '-7' to each side of the equation.
7 + -7 + 9b = 0 + -7
Combine like terms: 7 + -7 = 0
0 + 9b = 0 + -7
9b = 0 + -7
Combine like terms: 0 + -7 = -7
9b = -7
Divide each side by '9'.
b = -0.7777777778
Simplifying
b = -0.7777777778</span>
You might be interested in
Answer:
0
Step-by-step explanation:
9x+6=9x+6
-9x-6
0
Answer:
1
Step-by-step explanation:
D. is the answer since (-8)(-24)=192 and so does (-16)(-12)
1, 4, 9, 16, 25,... ![n^{2}](https://tex.z-dn.net/?f=n%5E%7B2%7D)
Can’t see it at all post it again